CAN A RAPID ACCESS NEUROLOGY CLINIC REDUCE A&E ADMISSIONS?. Issue 10 (9th September 2014) - Peukert, Thomas; McDonnell, Gavin; Craig, John
Abstract : Background: The number of patients attending A&E with neurological symptoms in Northern Irelands largest hospital has more than doubled in the past nine years. Over half of those that present to A&E will be admitted; more patients are admitted with neurological symptoms than gastroenterology or cardiology. Objectives: To pilot a rapid access neurology clinic (RANC) and examine its effect on hospital admissions. Methods: The pilot ran for four weeks from October to November 2013. Three clinics were held per week with 4 slots available per clinic; slots were filled directly by senior A&E staff. Results: A total of 45 patients were seen in the RANC and 28 admissions were avoided. The average waiting time to be seen was 8 days. The two main presentations referred to the RANC were headaches and seizure. The average hospital stay for a patient with a neurological presentation admitted to the medical ward is 5.5days at a cost of £541 per day; by avoiding 154 hospital nights cost savings were calculated at £83, 314. Conclusion: Regular access to a RANC could lead to a reduction of unnecessary hospital admissions and substantial cost savings.